Respuestas

2013-03-19T19:35:22+01:00

-7xy=0                                                     2x-3y=0

xy=7+0                                                    -1xy=0

xy=7                                                          xy=1+0

                                                                    xy=1

  • Usuario de Brainly
2013-03-19T19:42:31+01:00

Uhmm , veamos :

 

     [ -3x -4y = 0] *(2)

      [2x -3y = 0 ]*(3)

--------------------------

      -6x -8y = 0

        6x -9y = 0

  ---------------------

        -8y - 9y = 0

            -17y = 0

                  y = 0 /-17

                  y = 0

 

Tenemos "y" , ahora hallemos "x" solo remplazando en cualquiera de nuestras dos ecuaciones :

 

    -3x -4y = 0

    -3x - 4*(0) = 0

      -3x - 0 = 0

         -3x = 0

              x = 0/-3

              x = 0

 

CS {  0 , 0 } 

 

SaLuDos :)''